1981
DOI: 10.1007/bf00618773
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long-term beta-blockade with alprenolol on platelet function and fibrinolytic activity in patients with coronary heart disease

Abstract: In 14 patients with coronary heart disease the effect of long-term treatment (mean 16 months, range 12-33) with alprenolol on platelet function and fibrinolytic activity was studied. While on the beta-blocker and two weeks after gradual withdrawal of it, the patients performed a bicycle-ergometer test and blood samples were obtained before and following exercise. Pre-exercise fibrinolytic activity, assessed by the euglobulin clot lysis time, was 183 +/- 27 min (mean +/- SEM) while on alprenolol as compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Because some of them are hydrophilic and do not cross the blood–brain barrier, 131,132 a direct effect on central neural mechanisms seems unlikely. Many β ‐blockers decrease platelet aggregability (propranolol, 133 metoprolol, 134 pindolol, 134 practolol, 135 esmolol, 136 carvedilol, 137 alprenolol, 138 atenolol 133 ), probably by increased PGI 2 formation in the arterial wall 135 . Also, the prophylactic effect of calcium antagonists might be associated with their well‐known antiplatelet effect 139 .…”
Section: Prophylactic Action Of Calcium and β‐Blockersmentioning
confidence: 99%
“…Because some of them are hydrophilic and do not cross the blood–brain barrier, 131,132 a direct effect on central neural mechanisms seems unlikely. Many β ‐blockers decrease platelet aggregability (propranolol, 133 metoprolol, 134 pindolol, 134 practolol, 135 esmolol, 136 carvedilol, 137 alprenolol, 138 atenolol 133 ), probably by increased PGI 2 formation in the arterial wall 135 . Also, the prophylactic effect of calcium antagonists might be associated with their well‐known antiplatelet effect 139 .…”
Section: Prophylactic Action Of Calcium and β‐Blockersmentioning
confidence: 99%
“…We performed prospective validation on 22 predicted compounds that have not been used as anticoagulants, and found that their coagulation activity is significantly lower than the negative controls. Among the 22 compounds, several have been reported to affect coagulation in previous research, such as labetalol and alprenolol . Four newly predicted compounds with lowest coagulation activity share a mutual target protein, ADRB2.…”
Section: Discussionmentioning
confidence: 90%
“…In the one previous study [14] examining the effect of fl-adrenoceptor blockade on fibrinolysis in patients with ischaemic heart disease, which predated assays of t-PA and PAI-1, alprenolol (a nonselective beta blocker with ISA) prolonged euglobulin clot lysis time at rest but did not influence the response to exercise. Metoprolol caused no change in PAI-1 in 10 normal subjects [15], but in 15 hypertensive patients it caused a decrease [16].…”
Section: Discussionmentioning
confidence: 99%